Preparation and Evaluation of Some Properties of Heat Cured Acrylic Based Denture Soft Liner - Basima M. A. MA Hussein; Salem A Salem; Salah M Aliwi (College of Dentistry/ University of Baghdad, 2015)
Background: The base of the denture is largely responsible for providing the prosthesis with retention, stability, and support by being closely adapted to the oral mucosa. However; the process of bone resorption is irreversible and may lead to an inadequate fit of the prosthesis; this can be overcome by relining. Materials and methods: Acrylic based soft denture liner is prepared by preparing polymer from purified methylmethacrylate monomer with (10-2) initiator and (30%) dibutylphthalate plasticizer concentrations. Biological properties were evaluated in comparison with the control material through subcutaneous specimens' implantation in the New Zealand rabbits. Excisional biopsies were taken after (1, 3, days 1, 2, 3, 4 weeks) period. Microscopically, sections are studied to explore the consequences of thecontact with tested material and tissue response. Tensile strength, percentage of elongation, compressive, bond, and peel strengthwere evaluated; as well as water sorption and solubility is compared with the control material. Results: Histological study of the sections contained experimental and control materials showed normal tissue response by normal infiltration of the inflammatory cells; acute in the first days then chronic inflammatory cells were seen in the subsequent periods. Finally capsular enclosure of the specimens was well characterized and seen after 4 weeks. Results of the mechanical properties showed non-significant differences for the tested properties except the percentage of elongation; control material recorded significantly higher value. Moreover, statistically; water sorption of the experimental material was significantly lower than the control material; while the tested materials showed non-significant differences regarding the solubility test. Conclusion: The recommended formula of preparing heat-cured; acrylic based denture soft liner showed acceptable properties. Further evaluations of the experimental material were suggested.